Pendampingan Baca Puisi dalam Rangka Lomba FLS2N Kabupaten Trenggalek Tahun 2024 - Fahrudin Fahrudin (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Poetry as a form of literary work includes a variety of feelings. The role of poetry is very large, given that poetry has a very large impact on life in society. Regarding poetry that is read or performed in a competition event as big as FLS2N means that it also provides a separate experience for connoisseurs of this type of literary work. Literary works of poetry give literary connoisseurs a taste of their own. The holding of this poetry reading competition event makes poetry reading at the school level grow and develop. In addition, the activity becomes a spectacle as well as an achievement event for the school.